Ferromanganese erosion resistant refractory material and preparation method thereof

By using ASC brick base material, barium zirconate or zirconium silicate modified filler and magnesium phosphate, aluminum phosphate and tungsten carbide interface isolation materials in refractory materials, the micropore formation and instability of the interface isolation layer caused by ferromanganese erosion are solved, and the corrosion resistance and life of the material are improved.

CN120423863AActive Publication Date: 2025-08-05GONGYI TIANYU REFRACTORY MATERIALS
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510572505.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-06
Publication Date
2025-08-05
Estimated Expiration
2045-05-06

AI Technical Summary

Technical Problem

When existing refractory materials face erosion of ferromanganese, carbon oxidation leads to the formation of micropores, the melting point of the reactive metamorphic layer decreases, and the interface isolation layer is unstable, resulting in a shortening of the life of the refractory material.

Method used

A combination of ASC brick base material, barium zirconate or zirconium silicate modified filler and magnesium phosphate, aluminum phosphate, and tungsten carbide interface isolation materials are used to prevent carbon oxidation and erosion of manganese by forming a high melting point protection barrier and dynamic isolation layer on the surface.

Benefits of technology

It significantly improves the corrosion resistance and service life of refractory materials, prevents erosion from growing internally, and enhances the density and stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120423863A_ABST
    Figure CN120423863A_ABST
Patent Text Reader

Abstract

The invention relates to the field of refractory materials, in particular to a ferromanganese erosion-resistant refractory material and a preparation method thereof, and solves the problems that the existing refractory material is eroded by ferromanganese for a long time, carbon element oxidation causes micropores in the refractory material, a melting point decline boundary layer of a reaction metamorphic layer is unstable, and the ferromanganese erosion surface grows into the refractory material; a working layer is composed of, by weight, 80-95 parts of ASC brick base materials, 2-7 parts of modified filling materials and 10-20 parts of interface isolation materials, the modified filling materials are barium zirconate or zirconium silicate, the modified materials are tantalum nitride, and the mass ratio of the filling materials to the tantalum nitride is (1-6): 1. The interface isolation material is composed of magnesium phosphate, aluminum phosphate and tungsten carbide, and the mass ratio of magnesium phosphate to aluminum phosphate to tungsten carbide is (4-6): (4-6): (8-12). According to the invention, the refractory material has extremely high ferromanganese tolerance, and the service life of the refractory material is greatly prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of refractory materials, and in particular to a refractory material capable of withstanding ferromanganese corrosion and a preparation method thereof. Background Art

[0002] The development of refractory materials involves multiple stages. Initially, high-alumina bricks were used, which contained silicon dioxide, which would increase the silicon content in the molten steel. Therefore, aluminum-magnesium-carbon bricks were developed. However, carbon composite materials have poor oxidation resistance and low strength, so people switched to silicon carbide composite materials. Carbon will cause carbon increase in the molten steel, so it has developed into low-carbon magnesium nitride aluminum oxide, which can effectively handle high-temperature molten iron. The current development and research on medium and high manganese steels show that manganese steel has excellent strength and wear resistance, and is a project material in the fields of heavy industry and machinery manufacturing.

[0003] However, the presence of manganese in ferromanganese molten iron has a great destructive effect on refractory materials. A large amount of black-green substance is often generated on the surface of refractory materials in contact with high manganese steel. This substance is the manganese element in manganese steel oxidized into manganese monoxide impurities. Therefore, the use of silica-based inorganic refractory materials is not advisable. Nowadays, ASC bricks are mostly used as the mainstream choice for ferromanganese molten iron. However, it is found during long-term use that the actual service life of this material is not long. The oxidation rate of carbon is affected by the oxides of manganese and iron, and the oxidation rate of carbon becomes faster. The carbon content in ASC bricks accounts for about 30%, so for a long time Under interstitial corrosion, more micropores will be produced. Other refractory materials are composed of oxides. Under high temperature conditions, refractory oxides will dissolve or decompose, thereby increasing the content of other impurity elements in the molten steel. As the dissolution proceeds, an interface isolation layer will gradually form between the molten steel and the refractory material, and the manganese element will transfer back to the refractory material. During the transfer of the manganese element, it reacts with the oxidizing substances in the interface isolation layer to form a reaction metamorphic layer with a lower melting point, resulting in the collapse of the stable interface isolation layer, thereby allowing the manganese steel molten steel to invade the new refractory material, pushing the interface isolation layer to grow into the interior of the refractory material.

[0004] The above are the problems that existing refractory materials face when facing ferromanganese molten iron. One is that the carbon element is oxidized to form pores, and the molten steel penetrates inward along the pores. The other is that the interface insulation layer formed by the molten steel and the refractory material has a lower melting point and is eroded inward. Summary of the Invention

[0005] In order to solve the problems that the existing refractory materials are corroded by ferromanganese for a long time, carbon oxidation causes micropores in the refractory materials, the melting point of the reaction metamorphic layer on the surface of the refractory materials decreases, the boundary layer is unstable, and the ferromanganese corrosion surface grows inside the refractory materials, resulting in a short service life of the refractory materials, the present invention provides a refractory material resistant to ferromanganese corrosion and a preparation method thereof.

[0006] The technical solution adopted by the present invention is as follows:

[0007] A refractory material resistant to ferromanganese corrosion, comprising a permanent layer and a working layer, wherein the working layer is composed, by weight, of 80-95 parts of an ASC brick base material, 2-7 parts of a modified filler, and 10-20 parts of an interface insulating material;

[0008] The modified filler is barium zirconate or zirconium silicate, the modified material is tantalum nitride, and the mass ratio of the filler material to the tantalum nitride is 1-6:1;

[0009] The interface isolation material consists of magnesium phosphate, aluminum phosphate and tungsten carbide, and the mass ratio of magnesium phosphate, aluminum phosphate and tungsten carbide is 4-6:4-6:8-12.

[0010] This application uses high-melting-point materials such as barium zirconate or zirconium silicate to construct a complex anti-erosion filling layer on the basis of existing ASC bricks, and modifies the surface with tantalum nitride to block the pores to prevent the carbon element from being oxidized to form an erosion path. Using barium zirconate or zirconium silicate as the filling layer not only has high material strength and can be used for a long time, but also enhances the density of the surface of the ASC brick during the modification process, making it more resistant to ferromanganese corrosion.

[0011] Zirconium can form a protective barrier with a high melting point at high temperatures, significantly improving the material's corrosion resistance. It also has a certain thermal expansion coefficient at high temperatures, which can block gaps at high temperatures and prevent ferromanganese and molten iron from corroding the interior. Tantalum is used as a modified material for filling substances. Its function lies in its extremely high melting point, which is much higher than the melting point of metals. It will not react with molten steel, protecting the internal "filling blockage" barium zirconate or zirconium silicate from damage. Tantalum also forms tantalum nitride in the subsequent preparation process. The density of TaN is about 10% lower than that of Ta, which greatly increases the density of the porous material and effectively seals the pores.

[0012] Secondly, magnesium phosphate, aluminum phosphate and tungsten carbide are used as the outermost layer of the refractory material. The tungsten carbide skeleton and the immiscible magnesium phosphate phase and aluminum phosphate phase are used as dynamic insulation layers to prevent the erosion of ferromanganese steel liquid. Magnesium phosphate and aluminum phosphate melt at 1200-1400 to form a semi-solid viscous layer. The viscous layer can flow and replenish in the microcracks, thereby maintaining the integrity of the refractory surface. The most important thing is that magnesium phosphate and aluminum phosphate are in ionic state at high temperature and belong to ionic structure, while molten steel is a metal structure. The two are not soluble in each other. Therefore, the dynamic liquid phase layer of magnesium phosphate and aluminum phosphate prevents direct contact between molten steel and refractory material, prevents the dissolution and collapse of refractory material, and improves the service life of refractory material.

[0013] Preferably, the ASC brick base material is formed by mixing and sintering 45-65 parts of corundum, 15-25 parts of silicon carbide, 10-20 parts of graphite, 8-12 parts of aluminum dihydrogen phosphate and 2-3 parts of pure aluminum powder in parts by weight.

[0014] Preferably, the graphite has a particle size of 0.125-0.500 mm, wherein the graphite with a particle size of 0.125-0.300 mm accounts for 60%, and the graphite with a particle size of 0.300 mm-0.500 mm accounts for 40%.

[0015] Graphite with this specific gravity can generate sufficient pores for filling and forming barium zirconate or zirconium silicate and tantalum nitride, and the pores are neither too few nor too large.

[0016] Preferably, the permanent layer is composed of 60-70 parts by weight of aluminum oxide, 5-10 parts by weight of aluminum silicate, 5-8 parts by weight of silicon powder, 15-20 parts by weight of silicon dioxide and 0.1-1 part by weight of sodium tripolyphosphate.

[0017] The present application also provides a method for preparing the above-mentioned refractory material resistant to ferromanganese corrosion, and the specific preparation steps are as follows:

[0018] S1. Construction of the microporous structure of ASC bricks: heating the ASC bricks to 650-750°C for heat treatment in an oxygen atmosphere for 2-4 hours at an atmosphere introduction rate of 5-10 L / min, and then cooling to obtain a surface porous base material;

[0019] S2. Preparation of modified filler: placing the surface porous base material in an aqueous solution of zirconium oxychloride, and adding ammonia water dropwise to form a precipitate. Then, the surface porous base material is taken out and placed in an ethylenediamine solution of a barium salt, stirred and heated, and reacted at 160-220° C. for 12-36 hours, and washed to obtain the loaded porous base material;

[0020] Then the loaded porous base material is modified, and the specific modification steps are as follows:

[0021] Tantalum powder is coated on the surface of the loaded porous base material, and then heat-treated at high temperature in an ammonia atmosphere, and then placed in a nitrogen-containing electrolyte for electric treatment for 0.5-2 hours with a pulse current of 10-100 kHz to obtain a modified filler;

[0022] S3. Preparation of interface isolation material: weigh magnesium phosphate, aluminum phosphate and tungsten carbide and mix them to obtain isolation material, press the isolation material onto the outside of the modified filler by cold isostatic pressing to form a rough billet, and heat treat the rough billet to form an interface isolation material.

[0023] The present application removes the graphite on the surface of the ASC brick by heat treatment under an oxygen atmosphere, thereby forming multiple small microporous gaps, which serve as filling sites for the filler. The filler is filled by hydrothermally treating a solution of zirconium oxychloride and barium salt to form a solid precipitate that is precipitated in the microporous gaps. The subsequent tantalum nitride modification uses electrolytic treatment to form a denser nitride layer and can repair surface defects in the previous hydrothermal treatment process. The selected pulse current can promote the rapid diffusion of nitrogen atoms. The volume expansion during the nitriding process will not destroy the continuity of the surface, but will grow along the microporous surface and the gaps of the filler, thereby obtaining a higher quality nitride layer with extremely strong corrosion resistance.

[0024] Preferably, the cooling in step S1 is uniform cooling, and the cooling rate is 50° C. / h.

[0025] Preferably, the addition ratio of the zirconium oxychloride and the barium salt is 1:1, and the concentrations of the zirconium oxychloride and the barium salt are both 5-50 mmol / mL, and the concentration of the ammonia water is 30 wt%.

[0026] Preferably, the temperature of the high temperature treatment in the ammonia atmosphere in step S2 is 800-1000°C.

[0027] Preferably, the nitrogen-containing electrolyte in step S2 is an organic-inorganic composite electrolyte, the organic substance is urea, ethylenediamine or melamine, and the inorganic material is ammonium nitrate, potassium nitrate, ammonium sulfate or ammonium phosphate.

[0028] Preferably, in step S3, the isostatic pressing pressure of the isolation material is 300-600 MPa, the isostatic pressing time is 5-10 min, the heat treatment temperature is 1200-1350°C, the heat treatment time is 3-12 h, and Co or Ni is added as a sintering binder, and the amount of the sintering binder used is 2-4%.

[0029] The beneficial effects of the present invention are:

[0030] 1. The present application coarsens the graphite components on the surface of the refractory material that are easily oxidized, fills the micropores with a high-melting-point blocking material through a hydrothermal reaction, and electrolyzes a layer of tantalum nitride with an extremely high melting point on the surface. The volume expansion under the electrochemical change is utilized to densify the surface of the refractory material, thereby greatly improving the corrosion resistance of the refractory material. It is a solution to prevent molten steel from penetrating into the interior of the refractory material along the pores.

[0031] 2. This application uses magnesium phosphate and aluminum phosphate that are in ionic state at high temperature and are insoluble in manganese steel liquid as a dynamic insulation layer, and the tungsten carbide skeleton serves as the attachment skeleton of liquid phase magnesium phosphate and aluminum phosphate, which can stabilize the liquid phase layer of magnesium phosphate and aluminum phosphate and not be affected by other external forces. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 Graph showing experimental data of embodiments of the present invention and comparative examples.

[0033] Figure 2 Graph showing experimental data of embodiments of the present invention and comparative examples. DETAILED DESCRIPTION

[0034] The following will refer to the attached Figures 1 to 2 The embodiments of the present invention are described in detail. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the scope of protection of the present invention.

[0035] Preparation Example 1

[0036] Preparation of ASC bricks

[0037] Weigh 50 parts of corundum, 20 parts of silicon carbide, 15 parts of graphite, 10 parts of aluminum dihydrogen phosphate and 2.5 parts of pure aluminum powder. The graphite with a particle size of 0.125-0.500 mm is selected, of which the graphite with a particle size of 0.125-0.300 mm accounts for 60%, and the graphite with a particle size of 0.300 mm-0.500 mm accounts for 40%. The lumps are crushed into particles with a particle size of 0.5-5 mm. After mixing all the weighed materials, 12% of the dry material mass of water is added to prepare a rough blank, which is placed in a sintering furnace for oxygen-free firing at a firing temperature of 1650°C and a firing time of 12 hours to obtain an ASC brick base material.

[0038] Preparation Example 2 - Selecting graphite with extremely small particle size

[0039] Preparation of ASC bricks

[0040] Weigh 45 parts of corundum, 15 parts of silicon carbide, 10 parts of graphite, 8 parts of aluminum dihydrogen phosphate and 2 parts of pure aluminum powder. Select graphite powder with a particle size of less than 0.125 mm. Crush the lumps into particles with a particle size of 0.5-5 mm. After mixing all the weighed materials, add 12% water by weight of the dry material to prepare a rough blank, and place it in a sintering furnace for oxygen-free firing at a firing temperature of 1500°C and a firing time of 10 hours to obtain an ASC brick base material.

[0041] Preparation Example 3 - Graphite Particle Size is Too Large

[0042] Preparation of ASC bricks

[0043] Weigh 65 parts of corundum, 25 parts of silicon carbide, 20 parts of graphite, 12 parts of aluminum dihydrogen phosphate and 3 parts of pure aluminum powder. Select graphite with a particle size greater than 0.500 mm. Crush the lumps into particles with a particle size of 0.5-5 mm. After mixing all the weighed materials, add 12% water by weight of the dry material to prepare a rough blank, and place it in a sintering furnace for oxygen-free firing at a firing temperature of 1750°C and a firing time of 20 hours to obtain an ASC brick base material.

[0044] Example 1

[0045] Preparation of refractory materials resistant to ferromanganese corrosion

[0046] S1. The ASC brick prepared in Preparation Example 1 was placed in oxygen and heated to 700°C for 3 hours at an oxygen introduction rate of 8 L / min. The brick was then cooled to room temperature at a uniform rate of 50°C / h to obtain a surface porous base material.

[0047] S2, weighing 90 parts by weight of the surface porous base material and placing it in a 20 mmol / mL zirconium oxychloride aqueous solution, adding 30 wt% ammonia water to the solution, after sufficient reaction, taking out the surface porous base material and placing it in a 20 mmol / mL barium salt ethylenediamine solution, the molar addition ratio of zirconium oxychloride to barium salt being 1:1, stirring and reacting, placing the surface porous base material and the barium salt ethylenediamine solution at a temperature of 200° C. for 20 hours, and washing with clean water to obtain a loaded porous base material, which has an increased weight of 3 parts by weight compared to the surface porous base material in S1;

[0048] Tantalum powder with a particle size of 20-50 microns is coated on the surface of a loaded porous base material, which is then placed in an ammonia atmosphere and heated to 900°C for heat treatment. Then, a 60wt% inorganic nitrogen ammonium nitrate aqueous solution is weighed and prepared. Organic nitrogen urea is weighed and added to the 60wt% inorganic nitrogen ammonium nitrate aqueous solution to form a composite electrolyte with a urea concentration of 30wt%. The loaded porous base material is placed in the electrolyte, and the composite electrolyte is energized with a pulse current of 60kHz for 1 hour to obtain a modified filler. The modified filler has an increased weight of 1 part by weight compared to the loaded porous base material.

[0049] S3. Weigh magnesium phosphate, aluminum phosphate and tungsten carbide in a mass ratio of 5:5:10 and mix to obtain an isolation material. Cold isostatically press 15 parts by weight of the isolation material onto the outside of the modified filler to form a rough billet at a pressure of 450 MPa and a cold isostatic pressing time of 8 minutes. Heat treat the rough billet at a heat treatment temperature of 1300°C and a heat treatment time of 8 hours to form an interface isolation material, thereby obtaining a refractory material resistant to ferromanganese corrosion.

[0050] Example 2

[0051] Preparation of refractory materials resistant to ferromanganese corrosion

[0052] S1. The ASC brick prepared in Preparation Example 1 was placed in oxygen and heated to 650°C for 2 hours at an oxygen introduction rate of 5 L / min. The brick was then cooled to room temperature at a uniform rate of 50°C / h to obtain a surface porous base material.

[0053] S2, weighing 80 parts by weight of the surface porous base material and placing it in a 5 mmol / mL zirconium oxychloride aqueous solution, adding 30 wt% ammonia water to the solution, after sufficient reaction, taking out the surface porous base material and placing it in a 5 mmol / mL barium salt ethylenediamine solution, the molar addition ratio of zirconium oxychloride to barium salt is 1:1, stirring and reacting, placing the surface porous base material and the barium salt ethylenediamine solution at a temperature of 160 ° C. and heating the reaction for 12 hours, and washing with clean water to obtain a loaded porous base material, which has an increased weight of 1 part by weight compared to the surface porous base material in S1;

[0054] Tantalum powder with a particle size of 20-50 microns is coated on the surface of a loaded porous base material, and the material is placed in an ammonia atmosphere and heated to 800°C for heat treatment. Then, a 60wt% inorganic nitrogen ammonium sulfate aqueous solution is weighed and prepared. Then, organic nitrogen ethylenediamine is weighed and added to the 60wt% inorganic nitrogen ammonium sulfate aqueous solution to form a composite electrolyte with an ethylenediamine concentration of 30wt%. The loaded porous base material is placed in the electrolyte, and the composite electrolyte is energized with a pulse current of 10kHz for 0.5h to obtain a modified filler. The modified filler has an increased weight of 1 part by weight compared to the loaded porous base material.

[0055] S3. Weigh magnesium phosphate, aluminum phosphate and tungsten carbide in a mass ratio of 4:4:12 and mix to obtain an isolation material. Press 10 parts by weight of the isolation material onto the outside of the modified filler by cold isostatic pressing to form a rough billet at a pressure of 300 MPa and a cold isostatic pressing time of 5 minutes. Heat treat the rough billet at a heat treatment temperature of 1200°C and a heat treatment time of 3 hours to form an interface isolation material, thereby obtaining a refractory material resistant to ferromanganese corrosion.

[0056] Example 3

[0057] Preparation of refractory materials resistant to ferromanganese corrosion

[0058] S1. The ASC brick prepared in Preparation Example 1 was placed in oxygen and heated to 750°C for 4 hours at an oxygen introduction rate of 10 L / min. The brick was then cooled to room temperature at a rate of 50°C / h to obtain a porous surface base material.

[0059] S2, weighing 95 parts by weight of the surface porous base material and placing it in a 50 mmol / mL zirconium oxychloride aqueous solution, adding 30 wt% ammonia water to the solution, after sufficient reaction, taking out the surface porous base material and placing it in a 50 mmol / mL barium salt ethylenediamine solution, the molar addition ratio of zirconium oxychloride to barium salt is 1:1, stirring and reacting, placing the surface porous base material and the barium salt ethylenediamine solution at a temperature of 220 ° C. and heating the reaction for 36 hours, washing with clean water to obtain a loaded porous base material, which has an increased weight of 6 parts by weight over the surface porous base material in S1;

[0060] Tantalum powder with a particle size of 20-50 microns is coated on the surface of a loaded porous base material, which is then placed in an ammonia atmosphere and heated to 1000°C for heat treatment. Then, a 60wt% inorganic nitrogen ammonium phosphate aqueous solution is weighed and prepared. Organic nitrogen melamine is weighed and added to the 60wt% inorganic nitrogen ammonium phosphate aqueous solution to form a composite electrolyte with a melamine concentration of 30wt%. The loaded porous base material is placed in the electrolyte, and the composite electrolyte is energized with a pulse current of 100kHz for 2 hours to obtain a modified filler. The modified filler has an increased weight of 1 part by weight compared to the loaded porous base material.

[0061] S3. Weigh magnesium phosphate, aluminum phosphate and tungsten carbide in a mass ratio of 6:6:8 and mix to obtain an isolation material. Mix 20 parts by weight of the isolation material with 3% of the total weight of a Co sintering binder and press the mixture onto the outside of the modified filler by cold isostatic pressing to form a rough billet at a pressure of 600 MPa and a cold isostatic pressing time of 10 min. Heat treat the rough billet at a heat treatment temperature of 1350°C for 12 h to form an interface isolation material, thereby obtaining a refractory material resistant to ferromanganese corrosion.

[0062] Comparative Example 1--ASC brick prepared by Preparation Example 2

[0063] Preparation of refractory materials resistant to ferromanganese corrosion

[0064] S1. The ASC brick prepared in Preparation Example 2 was placed in oxygen and heated to 700°C for 3 hours at an oxygen introduction rate of 8 L / min. The brick was then cooled to room temperature at a uniform rate of 50°C / h to obtain a surface porous base material.

[0065] The remaining steps are the same as those in Example 1.

[0066] Comparative Example 2 - ASC bricks prepared in Example 3

[0067] Preparation of refractory materials resistant to ferromanganese corrosion

[0068] S1. The ASC brick prepared in Preparation Example 3 was placed in oxygen and heated to 700°C for 3 hours at an oxygen introduction rate of 8 L / min. The brick was then cooled to room temperature at a uniform rate of 50°C / h to obtain a surface porous base material.

[0069] The remaining steps are the same as those in Example 1.

[0070] Comparative Example 3: ASC bricks without microporous structure

[0071] Preparation of refractory materials resistant to ferromanganese corrosion

[0072] S1. Weigh 90 parts by weight of the ASC brick prepared in Preparation Example 1 and place it in a 20 mmol / mL aqueous zirconium oxychloride solution. Add 30 wt% ammonia water dropwise to the solution. After sufficient reaction, take out the ASC brick and place it in a 20 mmol / mL ethylenediamine solution of barium salt. The molar addition ratio of zirconium oxychloride to barium salt is 1:1. After stirring for reaction, heat the ASC brick and the ethylenediamine solution of barium salt at 200°C for 20 hours. Wash with clean water to obtain a loaded ASC brick. The loaded ASC brick is 3 parts by weight heavier than the ASC brick in S1.

[0073] Tantalum powder with a particle size of 20-50 microns is coated on the surface of a loaded ASC brick, which is then placed in an ammonia atmosphere and heated to 900°C for heat treatment. Then, a 60wt% inorganic nitrogen ammonium nitrate aqueous solution is weighed and prepared. Organic nitrogen urea is weighed and added to the 60wt% inorganic nitrogen ammonium nitrate aqueous solution to form a composite electrolyte with a urea concentration of 30wt%. The ASC brick is placed in the composite electrolyte and the composite electrolyte is energized with a pulse current of 60kHz for 1 hour to obtain a modified ASC brick. The modified ASC brick has an additional 1 part by weight compared to the loaded ASC brick.

[0074] S2. Weigh magnesium phosphate, aluminum phosphate and tungsten carbide in a mass ratio of 5:5:10 and mix to obtain an isolation material. 15 parts by weight of the isolation material is pressed on the outside of the modified ASC brick by cold isostatic pressing to form a rough billet at a pressure of 450 MPa and a cold isostatic pressing time of 8 minutes. The rough billet is heat treated at a heat treatment temperature of 1300°C and a heat treatment time of 8 hours to form an interface isolation material, thereby obtaining a refractory material resistant to ferromanganese corrosion.

[0075] Comparative Example 4 - Filler without tantalum nitride modification

[0076] Preparation of refractory materials resistant to ferromanganese corrosion

[0077] S1. The ASC brick prepared in Preparation Example 1 was placed in oxygen and heated to 700°C for 3 hours at an oxygen introduction rate of 8 L / min. The brick was then cooled to room temperature at a uniform rate of 50°C / h to obtain a surface porous base material.

[0078] S2, weighing 90 parts by weight of the surface porous base material and placing it in a 20 mmol / mL zirconium oxychloride aqueous solution, adding 30 wt% ammonia water to the solution, after sufficient reaction, taking out the surface porous base material and placing it in a 20 mmol / mL barium salt ethylenediamine solution, the molar addition ratio of zirconium oxychloride to barium salt being 1:1, stirring and reacting, placing the surface porous base material and the barium salt ethylenediamine solution at a temperature of 200° C. for 20 hours, and washing with clean water to obtain a loaded porous base material, which has an increased weight of 3 parts by weight compared to the surface porous base material in S1;

[0079] S3. Weigh magnesium phosphate, aluminum phosphate and tungsten carbide in a mass ratio of 5:5:10 and mix to obtain an isolation material. Cold isostatically press 15 parts by weight of the isolation material onto the outside of the loaded porous base material to form a rough billet at a pressure of 450 MPa and a cold isostatic pressing time of 8 minutes. Heat treat the rough billet at a heat treatment temperature of 1300°C and a heat treatment time of 8 hours to form an interface isolation material, thereby obtaining a refractory material resistant to ferromanganese corrosion.

[0080] Comparative Example 5 - No tungsten carbide used in the interface isolation material

[0081] Preparation of refractory materials resistant to ferromanganese corrosion

[0082] S1. The ASC brick prepared in Preparation Example 1 was placed in oxygen and heated to 700°C for 3 hours at an oxygen introduction rate of 8 L / min. The brick was then cooled to room temperature at a uniform rate of 50°C / h to obtain a surface porous base material.

[0083] S2, weighing 90 parts by weight of the surface porous base material and placing it in a 20 mmol / mL zirconium oxychloride aqueous solution, adding 30 wt% ammonia water to the solution, after sufficient reaction, taking out the surface porous base material and placing it in a 20 mmol / mL barium salt ethylenediamine solution, the molar addition ratio of zirconium oxychloride to barium salt being 1:1, stirring and reacting, placing the surface porous base material and the barium salt ethylenediamine solution at a temperature of 200° C. for 20 hours, and washing with clean water to obtain a loaded porous base material, which has an increased weight of 3 parts by weight compared to the surface porous base material in S1;

[0084] Tantalum powder with a particle size of 20-50 microns is coated on the surface of a loaded porous base material, which is then placed in an ammonia atmosphere and heated to 900°C for heat treatment. Then, a 60wt% inorganic nitrogen ammonium nitrate aqueous solution is weighed and prepared. Organic nitrogen urea is weighed and added to the 60wt% inorganic nitrogen ammonium nitrate aqueous solution to form a composite electrolyte with a urea concentration of 30wt%. The loaded porous base material is placed in the electrolyte, and the composite electrolyte is energized with a pulse current of 60kHz for 1 hour to obtain a modified filler. The modified filler has an increased weight of 1 part by weight compared to the loaded porous base material.

[0085] S3. Weigh magnesium phosphate and aluminum phosphate in a mass ratio of 5:5 and mix to obtain an isolation material. Cold isostatically press 15 parts by weight of the isolation material onto the outside of the modified filler to form a rough billet at a pressure of 450 MPa and a cold isostatic pressing time of 8 minutes. Heat treat the rough billet at a heat treatment temperature of 1300°C and a heat treatment time of 8 hours to form an interface isolation material, thereby obtaining a refractory material resistant to ferromanganese corrosion.

[0086] Comparative Example 6: Tantalum powder was treated with electricity without using a nitrogen-containing electrolyte

[0087] Preparation of refractory materials resistant to ferromanganese corrosion

[0088] S1. The ASC brick prepared in Preparation Example 1 was placed in oxygen and heated to 700°C for 3 hours at an oxygen introduction rate of 8 L / min. The brick was then cooled to room temperature at a uniform rate of 50°C / h to obtain a surface porous base material.

[0089] S2, weighing 90 parts by weight of the surface porous base material and placing it in a 20 mmol / mL zirconium oxychloride aqueous solution, adding 30 wt% ammonia water to the solution, after sufficient reaction, taking out the surface porous base material and placing it in a 20 mmol / mL barium salt ethylenediamine solution, the molar addition ratio of zirconium oxychloride to barium salt being 1:1, stirring and reacting, placing the surface porous base material and the barium salt ethylenediamine solution at a temperature of 200° C. for 20 hours, and washing with clean water to obtain a loaded porous base material, which has an increased weight of 3 parts by weight compared to the surface porous base material in S1;

[0090] Tantalum powder with a particle size of 20-50 microns is coated on the surface of a loaded porous base material, and the material is placed in an ammonia atmosphere and heated to 900°C for heat treatment. Then, a 60wt% lithium hexafluorophosphate electrolyte is weighed and prepared. The loaded porous base material is placed in the electrolyte, and the electrolyte is energized with a pulse current of 60kHz for 1 hour to obtain a modified filler. The modified filler has an increased weight of 1 part by weight compared to the loaded porous base material.

[0091] S3. Weigh magnesium phosphate, aluminum phosphate and tungsten carbide in a mass ratio of 5:5:10 and mix to obtain an isolation material. Cold isostatically press 15 parts by weight of the isolation material onto the outside of the modified filler to form a rough billet at a pressure of 450 MPa and a cold isostatic pressing time of 8 minutes. Heat treat the rough billet at a heat treatment temperature of 1300°C and a heat treatment time of 8 hours to form an interface isolation material, thereby obtaining a refractory material resistant to ferromanganese corrosion.

[0092] Experiments and data

[0093] The refractory materials resistant to ferromanganese corrosion prepared in the above examples and comparative examples were used as inner linings and combined with an integrally cast permanent layer to form a ferromanganese ladle, wherein the permanent layer consisted of 65 parts by weight of aluminum oxide, 7 parts by weight of aluminum silicate, 6 parts by weight of silicon powder, 18 parts by weight of silicon dioxide, and 0.5 parts by weight of sodium tripolyphosphate. The refractory materials were tested for their ability to support ferromanganese molten iron. The specific experiments are as follows:

[0094] Thermal shock resistance test: Tested in accordance with GB / T30873-2014 standard. The unit is residual strength retention: %.

[0095] Oxidation resistance test: The test was conducted with reference to GB / T17732-2008 standard. The unit is oxide layer thickness: mm. The corrosion rate in Table 1 was tested under the conditions of a pouring time of 2 h, a pouring temperature of 1580°C, and a manganese content of 13.5%.

[0096] Corrosion resistance test: Refer to GB / T8931-2007 standard for testing, the unit is corrosion rate: %.

[0097] The specific data are shown in Table 1 below:

[0098] Table 1

[0099]

[0100]

[0101] The residual strength retention rate and erosion rate in Table 1 above are plotted as a line graph, as shown in FIG. Figure 1 shown.

[0102] The thickness of the oxide layer in Table 1 is plotted as a histogram. Figure 2 shown.

[0103] analyze

[0104] According to the data in Table 1, the refractory materials resistant to ferromanganese erosion in Example 1, Example 2 and Example 3 can withstand high-temperature molten iron with a manganese content of 15%, and can maintain good strength, with a low degree of erosion and very little oxidation. They can greatly improve their tolerance to ferromanganese molten iron and greatly improve the service life of the refractory materials.

[0105] According to the data in Table 1, the residual strength retention rate of the refractory material prepared in Comparative Example 1 is greatly reduced, the thickness of the oxide layer is medium, and the erosion rate is reduced. The difference between Comparative Example 1 and Example 1 is that the particle size of the graphite particles in the ASC brick is less than 0.125 mm, and the graphite particle size is related to the subsequent heat treatment and can significantly control the size of the pores generated during the heat treatment process. It can be proved that the appropriate graphite particle size can ensure the entry of the filler and the sealing effect of tantalum nitride, thereby improving the refractory performance of the refractory material.

[0106] According to the data in Table 1, the refractory material prepared in Comparative Example 2 has a serious decrease in residual strength retention rate, a medium oxide layer thickness, and a significant decrease in erosion rate. The difference between Comparative Example 2 and Example 1 is that the particle size of the graphite particles in the ASC bricks is greater than 0.500 mm. It can be proved that the appropriate graphite particle size ensures that the micropores will not be too large, and the appropriate particle size can also maximize the effect of heat treatment, and will not retain the carbon element involved in the oxidation of ferromanganese to form new pores, thereby greatly improving the strength and erosion resistance of the refractory material.

[0107] According to the data in Table 1, the refractory material prepared in Comparative Example 3 has a smaller decrease in residual strength retention rate, a larger oxide layer thickness, and a serious decrease in erosion rate. The difference between Comparative Example 3 and Example 1 is that the ASC brick does not construct a microporous structure. It can be proved that the establishment of the microporous structure can provide sufficient specific surface area, thereby depositing sufficient filling material to seal the pores and provide stronger blockage when eroded by ferromanganese, thereby improving the resistance to ferromanganese erosion.

[0108] According to the data in Table 1, the refractory material prepared in Comparative Example 4 has a smaller decrease in residual strength retention rate, a medium oxide layer thickness, and a greatly reduced erosion rate. The difference between Comparative Example 4 and Example 1 is that the filler is not modified with tantalum nitride. It can be proved that the modification of tantalum nitride can effectively seal the gaps generated by heat treatment, and the volume expansion from tantalum to tantalum nitride can greatly reduce the damage caused by ferromanganese erosion, thereby improving the performance of the refractory material.

[0109] According to the data in Table 1, the residual strength retention rate of the refractory material prepared in Comparative Example 5 is greatly reduced, the thickness of the oxide layer is small, and the erosion rate has decreased to a certain extent. The difference between Comparative Example 5 and Example 1 is that tungsten carbide is not used in the interface isolation material. It can be proved that the presence of tungsten carbide can ensure the stability of the outer liquid phase isolation layer to a certain extent, thereby indirectly improving the refractory performance of the refractory material, maintaining the isolation stability of the magnesium phosphate and aluminum phosphate ion phases, and thus improving the erosion of ferromanganese molten iron.

[0110] According to the data in Table 1, the refractory material prepared in Comparative Example 6 has a very little decrease in residual strength retention rate, a low oxide layer thickness, and a certain degree of decrease in erosion rate. The difference between Comparative Example 6 and Example 1 is that no nitrogen-containing electrolyte is used when the tantalum powder is subjected to electrical treatment. This proves that the nitriding treatment can ensure that a sufficient amount of tantalum nitride is generated, and fill and repair tiny gaps that are not completely covered, thereby isolating the erosion of ferromanganese and molten iron, thereby improving the performance of the refractory material.

[0111] Thus far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it will be readily understood by those skilled in the art that the scope of protection of the present invention is obviously not limited to these specific embodiments. Without departing from the principles of the present invention, those skilled in the art may make equivalent changes or substitutions to the relevant technical features, and the technical solutions after such changes or substitutions will fall within the scope of protection of the present invention.

Claims

1. A refractory material resistant to ferromanganese corrosion, comprising a permanent layer and a working layer, characterized in that: The working layer is composed of 80-95 parts by weight of ASC brick base material, 2-7 parts of modified filler and 10-20 parts of interface isolation material; The modified filler is barium zirconate or zirconium silicate, the modified material is tantalum nitride, and the mass ratio of the filler material to the tantalum nitride is 1-6:1; The interface isolation material consists of magnesium phosphate, aluminum phosphate and tungsten carbide, and the mass ratio of magnesium phosphate, aluminum phosphate and tungsten carbide is 4-6:4-6:8-12.

2. A refractory material resistant to ferromanganese corrosion according to claim 1, characterized in that: The ASC brick base material is prepared by mixing and sintering 45-65 parts of corundum, 15-25 parts of silicon carbide, 10-20 parts of graphite, 8-12 parts of aluminum dihydrogen phosphate and 2-3 parts of pure aluminum powder in parts by weight.

3. A refractory material resistant to ferromanganese corrosion according to claim 2, characterized in that: The graphite has a particle size of 0.125-0.500 mm, wherein the graphite with a particle size of 0.125-0.300 mm accounts for 60%, and the graphite with a particle size of 0.300 mm-0.500 mm accounts for 40%.

4. The refractory material resistant to ferromanganese corrosion according to claim 1, characterized in that: The permanent layer consists of 60-70 parts by weight of aluminum oxide, 5-10 parts by weight of aluminum silicate, 5-8 parts by weight of silicon powder, 15-20 parts by weight of silicon dioxide and 0.1-1 part by weight of sodium tripolyphosphate.

5. The method for preparing a refractory material resistant to ferromanganese corrosion according to any one of claims 1 to 4, characterized in that: The specific preparation steps are as follows: S1. Construction of the microporous structure of ASC bricks: heating the ASC bricks to 650-750°C for heat treatment in an oxygen atmosphere for 2-4 hours at an atmosphere introduction rate of 5-10 L / min, and then cooling to obtain a surface porous base material; S2. Preparation of modified filler: placing the surface porous base material in an aqueous solution of zirconium oxychloride, and adding ammonia water dropwise to form a precipitate. Then, the surface porous base material is taken out and placed in an ethylenediamine solution of a barium salt, stirred and heated, and reacted at 160-220° C. for 12-36 hours, and washed to obtain the loaded porous base material; Then the loaded porous base material is modified, and the specific modification steps are as follows: Tantalum powder is coated on the surface of the loaded porous base material, and then heat-treated at high temperature in an ammonia atmosphere, and then placed in a nitrogen-containing electrolyte for electric treatment for 0.5-2 hours with a pulse current of 10-100 kHz to obtain a modified filler; S3. Preparation of interface isolation material: weigh magnesium phosphate, aluminum phosphate and tungsten carbide and mix them to obtain isolation material, press the isolation material onto the outside of the modified filler by cold isostatic pressing to form a rough billet, and heat treat the rough billet to form an interface isolation material.

6. The method for preparing a refractory material resistant to ferromanganese corrosion according to claim 5, characterized in that: The cooling in step S1 is performed at a uniform speed, with a cooling rate of 50° C. / h.

7. The method for preparing a refractory material resistant to ferromanganese corrosion according to claim 5, characterized in that: The addition ratio of the zirconium oxychloride to the barium salt is 1:1, and the concentrations of the zirconium oxychloride and the barium salt are both 5-50 mmol / mL, and the concentration of the ammonia water is 30 wt%.

8. The method for preparing a refractory material resistant to ferromanganese corrosion according to claim 5, characterized in that: The temperature of the high temperature treatment in the ammonia atmosphere in step S2 is 800-1000°C.

9. The method for preparing a refractory material resistant to ferromanganese corrosion according to claim 5, characterized in that: In step S2, the nitrogen-containing electrolyte is an organic-inorganic composite electrolyte, the organic substance is urea, ethylenediamine or melamine, and the inorganic material is ammonium nitrate, potassium nitrate, ammonium sulfate or ammonium phosphate.

10. The method for preparing a refractory material resistant to ferromanganese corrosion according to claim 5, characterized in that: In step S3, the isostatic pressing pressure of the isolation material is 300-600 MPa, the isostatic pressing time is 5-10 min, the heat treatment temperature is 1400-1500° C., the heat treatment time is 1-3 h, and Co or Ni is added as a sintering binder, and the amount of the sintering binder used is 2-4%.

Citation Information

Patent Citations

  • Method for controllably constructing phosphate coating layer and application thereof

    CN114373892A

  • Erosion-resistant light-weight refractory material and preparation method thereof

    CN114671673A

  • Alkali-resistant Al2O3-SiC-C brick, preparation method and application of alkali-resistant Al2O3-SiC-C brick on blast furnace cooling wall

    CN117303923A

  • High-bonding-strength oxidation-ablation-resistant composite coating for ceramic-based composite material and preparation method of high-bonding-strength oxidation-ablation-resistant composite coating

    CN119019179A

  • Alumina-carbonaceous refractory

    JP1993170524A